Comprehensive care from the perspective of health care workers from Belo Horizonte - Montenegro, Lívia Cozer; Penna, Cláudia Maria de Mattos; Brito, Maria José Menezes (Revista da Escola de Enfermagem da USP, 2010)
The objective of this qualitative case study was to present the understanding that health care workers and administrators of Belo Horizonte have about comprehensive care. Thirty-two workers were interviewed using a semi-structured questionnaire. Data analysis showed that comprehensiveness permeates the various levels of health care, adding the concept of health promotion. Interdisciplinary work emerges as a key element for the health care practice, which is made effective by sharing feelings. On the other hand, data show that comprehensive health care is only made effective provided that basic conditions are present, and services often do not provide those conditions. In conclusion, it is necessary to eliminate the fragmentations that exist in the form of health care organization as well as in the everyday practice of health care workers at the referred services so that it is possible to offer comprehensive, problem-solving care and humanize health care practices always aiming at the quality of life of the population.